Case series: imaging features of intraductal papillomas in patients presenting as nipple discharge - Dhull, Vedita; Sen, Jyotsna; Yadav, Rohtas; Drall, Nityasha (International Journal of Research in Medical Sciences, 2017)
Background:The purpose of this study was to evaluate imaging spectrum of intraductal papillomas on breast ultrasonography (US), mammography and contrast enhanced magnetic resonance imaging (CE- MRI) in patients presenting as nipple discharge. Methods: Our study was a prospective study of female patients presenting with the history of pathological nipple discharge. After taking detailed patient history, thorough clinical examination was conducted followed by multimodality imaging approach. The initial imaging work up began with ultrasonography and mammography, then followed by CE-MRI. Provisional diagnosis was given and compared with the final diagnosis achieved by surgery/ fine needle aspiration/ biopsy or clinical and imaging follow up. Results: 7/25 patients had intraductal papilloma as proven by surgery/ FNA. Mass lesion was identified in all 7 cases on sonography and MRI while it was detected in only 3 cases on mammography. Dilated ducts were demonstated in all 7 cases on sonography, in 6 cases on CE- MRI and 5 cases on mammography respectively. Conclusions: Mammography has limited diagnostic accuracy in patients with unexplained nipple discharge and MRI should be considered the diagnostic technique of choice in this clinical setting, with relevant corresponding area focussed on sonography.